2015
DOI: 10.1136/bmjopen-2014-007366
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure and incidence of heart failure and atrial fibrillation: a population-based prospective cohort study

Abstract: ObjectivesCadmium is a non-essential toxic metal with multiple adverse health effects. Cadmium has been shown to be associated with cardiovascular diseases, but few studies have investigated heart failure (HF) and none of them reported atrial fibrillation (AF). We examined whether cadmium exposure is associated with incidence of HF or AF.DesignA prospective, observational cohort study with a 17-year follow-up.SettingThe city of Malmö, Sweden.ParticipantsBlood cadmium levels were measured in 4378 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…Chronic, low-level Cd exposure in Sweden has been linked to an increased risk of heart failure (Borne et al 2015), while chronic, low-level Cd exposure in the U.S. been linked to death from CVD, heart disease, and coronary heart disease (Tellez-Plaza et al 2012) along with increased death from all causes (Hyder et al 2013;Patel et al 2013), cancer (Adams et al 2012;Lin et al 2014), and Alzheimer's disease (Min and Min 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic, low-level Cd exposure in Sweden has been linked to an increased risk of heart failure (Borne et al 2015), while chronic, low-level Cd exposure in the U.S. been linked to death from CVD, heart disease, and coronary heart disease (Tellez-Plaza et al 2012) along with increased death from all causes (Hyder et al 2013;Patel et al 2013), cancer (Adams et al 2012;Lin et al 2014), and Alzheimer's disease (Min and Min 2016).…”
Section: Resultsmentioning
confidence: 99%
“…An equivalent risk analysis of Cd exposure using blood Cd as an exposure biomarker gives parallel results: a reduction of blood Cd from 0.80 to 0.22 μg/L will prevent death from all causes and from CVD by 7% and 7.5%, respectively. Lifetime Cd exposure and heart disease onset have been evidenced from a 17-year follow-up of 4,378 Swedish men and women, aged 46-67 yrs, who had no history of either heart failure or atrial fibrillation (Borne et al 2015). Mean (range) of blood Cd in the Swedish sample group was 0.24 (range; 0.02-5.07) µg/L in men and the corresponding value in women was 0.27 (0.03-4.8) µg/ The symbol denotes modulation by essential elements such as zinc, iron and calcium.…”
Section: Cadmium Exposure and Mortalitymentioning
confidence: 99%
“…A prospective cohort study of 3,348 adults in the US also revealed a significant association between urine cadmium and increased incidence of heart failure 25. Meanwhile, a study of 4,378 participants in Sweden with a 17-year follow-up period demonstrated that the participants in the fourth quartile of blood cadmium levels had significantly higher incidence of heart failure than those in the first quartile 26. All of these findings suggest that elevated cadmium levels may exacerbate the critical condition and increase hospital mortality in AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the absorbed cadmium accumulates in the kidneys for a long time with a low rate of urinary excretion 6. Although cadmium exposure is a risk factor of cardiovascular diseases in humans,25,26 and may disturb myocardial metabolism (suggested by animal studies),22,23 it is uncertain whether the basic metabolism of cadmium would be changed in patients with cardiac diseases, including heart failure. Hence, further studies are needed to elucidate its specific role in AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium exposure is associated with diseases of atherosclerosis including peripheral arterial disease, stroke, ischemic heart disease, and acute coronary syndromes 182,190193 . Cadmium exposure has also been associated with incident heart failure, although it unclear what percentage of heart failure cases are ischemic versus nonischemic in etiology 182,192,194 . The largest studies of cadmium and cardiovascular disease are from US NHANES data and the Strong Heart Study of US Native Americans.…”
Section: Cadmiummentioning
confidence: 99%